Prussian Blue Analogs for Rechargeable Batteries - Wang, Baoqi; Han, Yu; Wang, Xiao; Bahlawane, Naoufal; Pan, Hongge; Yan, Mi; Jiang, Yinzhu (iScience, 2018)
Non-lithium energy storage devices, especially sodium ion batteries, are drawing attention due to insufficient and uneven distribution of lithium resources. Prussian blue and its analogs (Prussian blue analogs [PBAs]), or hexacyanoferrates, are well-known since the 18th century and have been used for hydrogen storage, cancer therapy, biosensing, seawater desalination, and sewage treatment. Owing to their unique features, PBAs are receiving increasing interest in the field of energy storage, such as their high theoretical specific capacity, ease of synthesis, as well as low cost. In this review, a general summary and evaluation of the applications of PBAs for rechargeable batteries are given. After a brief review of the history of PBAs, their crystal structure, nomenclature, synthesis, and working principle in rechargeable batteries are discussed. Then, previous works classified based on the combination of insertion cations and transition metals are analyzed comprehensively. The review includes an outlook toward the further development of PBAs in electrochemical energy storage. [Display omitted] Organometallic Chemistry; Electrochemical Energy Storage; Energy Materials